(untitled) (Journal of Economic Research & Business Administration, 2018)
This article examines the features of fair value measurement of equity investments in accordance with International Financial Reporting Standard (IFRS) 9 through other comprehensive income, without any deduction for disposal or disposal costs that the entity may incur in the sale or disposal of such investments. The standard requires that dividends received on these investments be recognized in profit or loss unless they represent a partial return on the value of the investment. Changes in the fair value of these investments will be recognized in other comprehensive income, and income and expenses will not be reclassified from other comprehensive income to profit or loss in the event of an impairment, sale or disposal of an investment. The unconditional advantage of such an instrument as fair value is the receipt of reliable information about the planned cash flows and the formation of a database of comparable information. The above is due to the fact that different assets can be purchased for a long period and, accordingly, accounted for at different prices. Based on the study of the structure of financial instruments of Kazakhstani organizations, it was concluded that one of the key issues in calculating depreciable cost is the determination of the effective interest rate less impairment.